Validity of proposed DSM-5 diagnostic criteria for nicotine use disorder: results from 734 Israeli lifetime smokers. Issue 10 (October 2013) - Shmulewitz, D.; Wall, M. M.; Aharonovich, E.; Spivak, B.; Weizman, A.; Frisch, A.; Grant, B. F.; Hasin, D.
<x content-type="archive" xml:space="preserve">Abstract</x> Background The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) proposes aligning nicotine use disorder (NUD) criteria with those for other substances, by including the current DSM fourth edition (DSM-IV) nicotine dependence (ND) criteria, three abuse criteria (neglect roles, hazardous use, interpersonal problems) and craving. Although NUD criteria indicate one latent trait, evidence is lacking on: (1) validity of each criterion; (2) validity of the criteria as a set; (3) comparative validity between DSM-5 NUD and DSM-IV ND criterion sets; and (4) NUD prevalence. Method Nicotine criteria (DSM-IV ND, abuse and craving) and external validators (e.g. smoking soon after awakening, number of cigarettes per day) were assessed with a structured interview in 734 lifetime smokers from an Israeli household sample. Regression analysis evaluated the association between validators and each criterion. Receiver operating characteristic analysis assessed the association of the validators with the DSM-5 NUD set (number of criteria endorsed) and tested whether DSM-5 or DSM-IV provided the most discriminating criterion set. Changes in prevalence were examined. Results Each DSM-5 NUD criterion was significantly associated with the validators, with strength of associations similar across the criteria. As a set, DSM-5 criteria were significantly associated with the validators, were significantly more discriminating than DSM-IV ND criteria, and led to increased prevalence of binary NUD (two or more criteria) over ND. Conclusions All findings address previous concerns about the DSM-IV nicotine diagnosis and its criteria and support the proposed changes for DSM-5 NUD, which should result in improved diagnosis of nicotine disorders.